Long-term follow-up of newborns at neurological risk - Enrico Gasparrini; Francesca Rosati; Maria Teresa Gaetti (BMC, 2019)
Abstract Background In order to give a new contribution to the knowledge of the psycho-physical, behavioral and socio-relational development of the individuals who were born at neurological risk, we have carried out a research work through a retrospective and observational analysis in such people, followed in their neuro-evolutionary development from the Department of Pediatrics and Neonatology of the Hospital of Jesi. The purpose of this work is to value the quality of life of the individuals born at neurological risk at a distance of time from the birth. In the literature only recently there are studies on the quality of life of some categories of people, but survey does not seem to be performed in individuals previously born at neurological risk. Methods A statistical descriptive and inferential survey has been carried out on 812 individuals who were born at neurological risk, 442 preterm newborns and 370 term newborns, followed from 1977 until to 2007. They were classed in order to their age at the time of our observation. We have submitted the entire sample to a Questionnaire to investigate some areas of their life, ranging from their clinical and psycho-social history to their personal coming of life. Then the same persons, subdivided according to the various age groups, were subjected to other Questionnaires on the quality of life, internationally used. Results Neurological outcomes were found in 14.7% of the preterm newborns and in 6% of the term newborns, with a significant correlation between neurological outcomes and gestational age, low birth-weight, hypoxic-ischemic encephalopathy and low APGAR-index. Neuro-disabilities were found prevalently belong to the small for gestational age preterm newborns. A low quality of life emerged in those who had neurological outcomes. Conclusions Our study on the individuals who were born at neurological risk, analyzed at a distance, shows that a good health is associated with a good quality of life, while a low quality of life occurs to those who had neurological outcome, especially in the physical, cognitive, emotional and socio-relational aspects. As far as the few neurological outcomes which we have found in this survey, we think that they are due, other than to the natural factors, also to the high quality of the obstetric and neonatal care, to the early habilitation physiotherapy and to the important collaboration with the family.